1993
DOI: 10.1161/01.res.72.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nitric oxide formation in the nucleus tractus solitarius increases renal sympathetic nerve activity in rabbits.

Abstract: It has been shown that nitric oxide (NO) is synthesized in the central nervous system as well as in vascular endothelial cells. However, the physiological role of NO in cardiovascular regulation by the central nervous system remains unclear. This objective of this study was to examine the possibility that NO plays a role in neural transmission in the nucleus tractus solitarius (NTS) and thus contributes to control of sympathetic nerve activity in rabbits. We examined the effects ofNG-monomethyl-L-arginine (L-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
167
0
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(181 citation statements)
references
References 19 publications
12
167
0
2
Order By: Relevance
“…It was suggested (17) that one central site at which NO may produce its sympathoinhibition is the nucleus tractus solitarius (NTS), where L -glutamate caused an L -NMMA and methylene blue reversible decrease in arterial blood pressure and heart rate in the rat (12), presumably mediated by NO (5). Moreover, L -NMMA injected directly into the NTS increased renal sympathetic nerve activity in rabbit (7). The NTS has reciprocal connections with a number of central structures, and is in a unique position to react to sensory information with the necessary alterations in autonomic tone.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested (17) that one central site at which NO may produce its sympathoinhibition is the nucleus tractus solitarius (NTS), where L -glutamate caused an L -NMMA and methylene blue reversible decrease in arterial blood pressure and heart rate in the rat (12), presumably mediated by NO (5). Moreover, L -NMMA injected directly into the NTS increased renal sympathetic nerve activity in rabbit (7). The NTS has reciprocal connections with a number of central structures, and is in a unique position to react to sensory information with the necessary alterations in autonomic tone.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 NTS neuronal activity was reduced by systemic injection of L-NAME at constant blood pressure 55 while L-arginine and the NO donor, sodium nitroprusside (SNP) increased discharge rate. 56 The RVLM, the final site of sympathetic processing in the brainstem, also appears to contain neurons susceptible to an inhibitory influence by NO.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…We have previously shown that NMDA receptors within the nucleus tractus solitarii (NTS) are integral to the baroreceptor reflex (12), and others have suggested that nitroxidergic mechanisms may play a role in cardiovascular control through the NTS (13)(14)(15)(16)(17). We have sought to test this hypothesis and determine if NO• released from donor compounds elicits cardiovascular responses when administered into the NTS, the primary site of termination of vagal and glossopharyngeal cardiovascular afferent nerves.…”
Section: Wt Talmanmentioning
confidence: 99%
“…There are abundant thiols in biological tissues (37) to support such a biosynthetic mechanism. Others have promoted a role for NO• in the NTS because of the actions of NOS inhibitors administered into the nucleus (13,38), but the difficulty in measuring authentic NO• and SNC in biological tissues (34) makes the direct application of these findings to NO • as the end product of NOS risky as well.…”
Section: Wt Talmanmentioning
confidence: 99%